Dental and Oral Hospital Health Service System in Indonesia - Pindobilowo; Lukas Kusparmanto; Dwi Ariani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Background: Oral and Dental Hospital provides health services, namely individual dental and oral health services for treatment and recovery services without neglecting health promotion and disease prevention services which are carried out through outpatient, emergency and medical treatment services. Purpose: to introduce the public to the health service system at the Dental and Oral Hospital, where people still do not understand about Dental and Oral Hospitals, especially in Indonesia. Methods: This literature study uses the narrative review method by analyzing various journals from the PubMed, Ebsco and Google Scholar databases from the last 5 years related to Oral and Dental Hospital. Conclusion: Oral and Dental Hospital provides facilities to improve the quality of service, education, research in the field of dental and oral health from basic to specialist levels in accordance with the demands of the community and developments in Medical and Dentistry Science and Technology, as well as being a means of referral efforts